Characteristics of bilateral symmetry detection - Šoliūnas, Alvydas; Gurčinienė, Ona (Psichologija, 2001)
Although the symmetry is detected very fast and without efforts, it is not known how this process is going on and what mechanisms make the detection of symmetry possible. This paper reviews the characteristics of the detection of various symmetry types giving the majority of attention to bilateral symmetry. The main theories and models of symmetry detection are discussed as well. Experimental part of the paper is devoted to extend the existing knowledge with experimental data which were obtained with the stimuli and procedure that differ from that used by other investigators. Test stimuli were figures consisting of four, six, seven, or eight horizontal and vertical line-segments, and the task for subjects was to answer what kind of stimulus was presented - vertically symmetrical, horizontally symmetrical, or asymmetrical. Test stimuli were presented very briefly (10 ms) followed by masking after 20-95 ms. Experimental results confirmed the advantage of vertical over horizontal symmetry. Number of line-segments did not influence the detection accuracy nor for vertical, nor for horizontal symmetry. Majority of subjects detected asymmetrical stimuli with the same accuracy as vertically symmetrical stimuli. Authors offer an experimental procedure that would enable to explain the role of attention in symmetry detection.